The Effect of Online Ship Ticket Sales Implementation and Infrastructure Development at the Port on Service Quality Improvement at PT. PELNI - Ratu Rania Azzahra; Linda Yulia Ayuningrum; Devi Marlita; M. Arif Hernawan (Jurnal Ilmu Multidisiplin, 2025)
This study aimed to assess the impact of ticket sales digitalization and port infrastructure on service quality at PT. PELNI, focusing on reducing ticket counter queues and improving operational efficiency. In the digital era, shipping companies are required to enhance service efficiency and convenience through adequate technology and infrastructure. Using a quantitative approach, data were collected from 122 respondents via a Likert scale questionnaire. The results indicate that while digitalization and port infrastructure collectively improve service quality, only port infrastructure independently has a significant effect. Although digitalization alone does not show a significant impact, it contributes to operational efficiency. This study provides practical insights for PT. PELNI, highlighting the importance of robust infrastructure development for service quality improvement, alongside the use of digital solutions to boost operational efficiency. The findings are expected to guide PT. PELNI’s management in enhancing customer satisfaction and competitiveness in the shipping industry.